Heparin functionalized polyaspartamide/polyester scaffold for potential blood vessel regeneration. Issue 5 (11th June 2013) - Pitarresi, Giovanna; Fiorica, Calogero; Palumbo, Fabio Salvatore; Rigogliuso, Salvatrice; Ghersi, Giulio; Giammona, Gaetano
Abstract An interesting issue in tissue engineering is the development of a biodegradable vascular graft able to substitute a blood vessel and to allow its complete regeneration. Here, we report a new scaffold potentially useful as a synthetic vascular graft, produced through the electrospinning of α, β‐poly(N‐2‐hydroxyethyl) (2‐aminoethylcarbamate)‐d, l‐aspartamide‐graft‐polylactic acid (PHEA‐EDA‐g‐PLA) in the presence of polycaprolactone (PCL). The scaffold degradation profile has been evaluated as well as the possibility to bind heparin to electrospun fibers, being it a known anticoagulant molecule able to bind growth factors. In vitro cell compatibility has been investigated using human vascular endothelial cells (ECV 304) and the ability of heparinized PHEA‐EDA‐g‐PLA/PCL scaffold to retain basic fibroblast growth factor has been evaluated in comparison with not heparinized sample. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1334–1341, 2014.